STD and Abortion Prevalence in Adolescent Mothers With Histories of Childhood Protection Involvement. Issue 4 (6th July 2015) - Cederbaum, Julie A.; Putnam‐Hornstein, Emily; Sullivan, Kathrine; Winetrobe, Hailey; Bird, Melissa
Abstract : CONTEXT: Early sexual debut and unprotected sexual activity place adolescents at risk of adverse sexual health outcomes. Adolescents involved with child protective services (CPS) may be a particularly vulnerable population. METHODS: California birth records for 86, 946 adolescents who became first‐time mothers in 2008–2010 were probabilistically linked to statewide CPS records from 1998 and later. The prevalence of STDs at birth and of abortion history were explored by preconception CPS involvement. Generalized linear models, adjusted for health, socioeconomic and demographic characteristics, were used to assess correlates of current STDs and history of abortion. RESULTS: At the time they gave birth, 1% of adolescents had a documented STD, and 5% reported a previous abortion. After adjustment for other characteristics, CPS involvement was associated with a significantly elevated prevalence both of STDs (relative risk, 1.2) and of previous abortion (1.4). Other characteristics also were associated with both outcomes, but not always in the same direction. For example, delaying prenatal care until after the first trimester or getting none at all was associated with an increased prevalence of STDs (1.3), but a reduced prevalence of abortion (0.8–0.9); having public insurance coverage for the birth was associated with a reduced STD prevalence (0.9) and an elevated abortion history prevalence (1.2). CONCLUSIONS: To assess whether adolescents with a history of CPS involvement need targeted sexual health interventions, further research is needed on the mechanisms that underlie associations between CPS involvement and adverse sexual health outcomes.